THE IMPACT OF WORKFORCE DIVERSITY AND CAREER DEVELOPMENT TOWARDS EMPLOYEES PERFORMANCE USING MULTIPLE LINEAR REGRESSION ANALYSIS (CASE IN MATAHARI DEPARTMENT STORE, MANADO) - Prasetio, Tio Riyandi; Lapian, S.L.H.V. Joyce; Rumokoy, Farlane S. (Universitas Sam Ratulangi, 2017)
Abstract: Performance is the result of work produced both in terms of quality and quantity of work and can be accounted for in accordance with its role within the organization or company, and accompanied by the ability, skills, and skills in completing the work and within a certain period. The purpose of this research is the investigation of the impact of workforce diversity and career development towards employee performance. Workforce diversity has been identified as one of the strategic capabilities that will add value to the organizations over their competition and Career Development is personal improvements do to achieve a career plan. This research is a quantitative research, which the data is obtained through questionare, and the data is analysed using the Multiple Linear Regression. The population of this research is the employees of Matahari Department Store in Manado, with 100 respondents of as the sample. The result shows that independent variables have a significant effect on dependent variable simultaneously. It means workforce diversity and career development have a significant effect on employee performance simultaneously. In partially test workforce diversity do not have positive significant effect on employee performance, Career development are the variables that show a large positive significant effect on employee performance.Â ÂÂKeywords: workforce diversity, career development, employee performance.